Imperfect inspection with directional information: A general failure probability model - Chun, Young H. (Journal of quality technology, 2019)
Suppose that the entire sequence of items produced is divided into a stream of nondefective items, followed by a stream of defective items. We propose a sequential inspection procedure for the production process that has a general failure probability-increasing, constant, or decreasing failure patterns. We also consider the inspector's classification errors as well as the costs of inspection and misclassifications. In numerical analysis, we show that other inspection models are special cases of our general model and analyze the effects of failure patterns on the inspection cost for various combinations of the type I and II errors.